Linked employer-employee data of firms' training costs : enriching register based LEE data with firm level data on apprenticeship training - Dietrich, Hans [Verfasser]; Alda, Holger [Verfasser]; Pfeifer, Harald [Verfasser]; Wenzelmann, Felix [Verfasser]; Schönfeld, Gudrun [Verfasser]; Schiel, Stefan [Verfasser]; Seth, Stefan [Verfasser] (My University, 2014)
"An important feature of apprenticeship training is the strong link between education and the labour market because a large part of the training takes place within firms. A considerable share of former apprentices are retained by the training firms, and this facilitates the transition of trainees from education to the labour market." One of the few examples of data sets representing the firm perspective of labour market transitions are the studies of the Federal Institute for Vocational Education and Training (Bundesinstitut für Berufsbildung, BIBB) on costs and benefits of apprenticeship training. This article deals with the latest of this BIBB surveys which was conducted in 2008 for the reference year 2007. It describes the merged data set that was obtained from two data sources: the Establishment Register (Betriebsdatei) of the Federal Employment Agency (Bundesagentur für Arbeit, BA) on the one hand and the firm specific data on the other hand. "Section 2 first describes the two data sources used for the merge and then addresses potential selectivity problems arising from a firm's option to decline the data merge. Section 3 discusses the quality of the match between survey and administrative data. Section 4 briefly summarizes the main results of the paper and sketches research perspectives of the matched data." (Text extract, BIBB-Doku)
Keywords: S 4 Kosten & Finanzierung; T 3.5 Statistik; Betriebliche Berufsausbildung; Ausbildungskosten; Kosten-Nutzen-Analyse; Datenanalyse; Datenaufbereitung; Quantitative Angaben